Filling the Gap : Infrastructure Investment in Brazil - Garcia-Escribano, Mercedes (IMF Working Papers; Working Paper ;, 2015)
Infrastructure bottlenecks have been identified as a key obstacle to growth affecting productivity and market efficiency, and hindering domestic integration and export performance. This paper assesses the state of Brazil's infrastructure, in light of past investment trends and various quality and quantity indicators. Brazil's infrastructure stock and its quality rank low in relation to that of comparator countries, chosen amongst main export competitors. We provide evidence that infrastructure affects domestic integration by analyzing price convergence of tradable goods across major cities. The government's concession program will narrow part of the infrastructure gap, however, governance reforms will be crucial to improving investment efficiency.